II International scientific conference «Regional economy: technologies, economy, ecology and infrastructure» (Kyzyl, 18-20 Oct. 2017.) - Soyan, Shonchalai Ch.; Balakina, Galina F. (The New Research of Tuva, 2018)
2nd International Scientific Conference “Regional economy: technology, economy, ecology and infrastructure” was held on Oct. 18-20, 2017 in Kyzyl in premises of the Tuvan Institute for Complex Development of Natural Resources of Siberian Branch of RAS. The conference was dedicated to studying and analyzing the regional economies, revealing the roots of the problems including disbalances in regional development, working out recommendations for solving the problems of regional development in modern conditions counting features of every region. Agenda of studies covered for main directions: “Socio-economical development of region: problems and prospects”, “Geology and natural potential of Tuva and bordering territories”, “Mathematical modelling and geoinformation cartography of natural and anthropomorphic processes”, “Rational use of natural resources and protection of environment”. This review presents the main messages of most interesting reports for sections. It defines the main outcome of the forum: scientific and practical conclusions, recommendation for administration of the Republic of Tuva in the fields of economy and environment protection.